Shelf–ocean exchange and hydrography west of the Antarctic Peninsula: a review. (14th May 2018) - Moffat, C.; Meredith, M.
Abstract : The West Antarctic Peninsula (WAP) is a highly productive marine ecosystem where extended periods of change have been observed in the form of glacier retreat, reduction of sea-ice cover and shifts in marine populations, among others. The physical environment on the shelf is known to be strongly influenced by the Antarctic Circumpolar Current flowing along the shelf slope and carrying warm, nutrient-rich water, by cold waters flooding into the northern Bransfield Strait from the Weddell Sea, by an extensive network of glaciers and ice shelves, and by strong seasonal to inter-annual variability in sea-ice formation and air–sea interactions, with significant modulation by climate modes like El Niño–Southern Oscillation and the Southern Annular Mode. However, significant gaps have remained in understanding the exchange processes between the open ocean and the shelf, the pathways and fate of oceanic water intrusions, the shelf heat and salt budgets, and the long-term evolution of the shelf properties and circulation. Here, we review how recent advances in long-term monitoring programmes, process studies and newly developed numerical models have helped bridge these gaps and set future research challenges for the WAP system. This article is part of the theme issue 'The marine system of the West Antarctic Peninsula: status and strategy for progress in a region of rapid change'.